Directed evolution of adenine base editors with increased activity and therapeutic application - Gaudelli, Nicole M; Lam, Dieter K; Rees, Holly A; Solá-Esteves, Noris M; Barrera, Luis A; Born, David A; Edwards, Aaron; Gehrke, Jason M; Lee, Seung-Joo; Liquori, Alexander J; Murray, Ryan; Packer, Michael S; et al. (Nature biotechnology, 2020)
The foundational adenine base editors (for example, ABE7.10) enable programmable A•T to G•C point mutations but editing efficiencies can be low at challenging loci in primary human cells. Here we further evolve ABE7.10 using a library of adenosine deaminase variants to create ABE8s. At NGG protospacer adjacent motif (PAM) sites, ABE8s result in ~1.5× higher editing at protospacer positions A5-A7 and ~3.2× higher editing at positions A3-A4 and A8-A10 compared with ABE7.10. Non-NGG PAM variants have a ~4.2-fold overall higher on-target editing efficiency than ABE7.10. In human CD34 cells, ABE8 can recreate a natural allele at the promoter of the γ-globin genes HBG1 and HBG2 with up to 60% efficiency, causing persistence of fetal hemoglobin. In primary human T cells, ABE8s achieve 98-99% target modification, which is maintained when multiplexed across three loci. Delivered as messenger RNA, ABE8s induce no significant levels of single guide RNA (sgRNA)-independent off-target adenine deamination in genomic DNA and very low levels of adenine deamination in cellular mRNA.